Improving the Performance of Planar Perovskite Solar Cells through Pre-heated, Delaying Annealing Process to Control Nucleation and Phase Transition of Perovskite Films - Sagar Jain (Crystal Growth & Design, 2019)
Obtaining good quality perovskite absorber film remains a challenging task that limits performance of planar perovskite solar cells. . In this work, we demonstrated the importance of pre-heating treatment on perovskite nucleation and phase transition. . Fine-tuning the appropriate pre-heating and standing time resulted in the formation of high quality perovskite films with enhanced optoelectronic properties.. Pre-heated perovskite films with delaying of 1 hour post-annealing achieved the hysteresis-free, record power conversion efficiency (PCE) of 16.18%. While the perovskite films without preheating treatment in solar cells shown only12.35% efficiency.. This improved performance with pre-heating treatment and delay annealing of perovskite films found as a result of homogeneous nucleation and formation of high quality perovskite films. Improved perovskite quality is further evidenced from enhanced optoelectronic and crystalline properties of the perovskite absorber after preheating treatment.